Ethical Values of Malangan Shadow Puppet Show from East Java in the Lakon of Kalakerna Gugat - Sudarsono, S. (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2014)
There are many values which an artist wants to express through a shadow puppet show in order to attract the attention of the audience. Malangan shadow puppet show acts not only as an entertainment but also as a guidance for character education. In the story of Kalakerna Gugat, ethical and aesthetic values in the story are in the form of etiquette in the dialogues or the characters. The value of having rights after completing duties becomes guidance for nobleness. Equality between rights and duties demanded by Kalakerna and propriety of characters are expressed straight to the point and they are easy to understand as well as entertaining. Impropriety in the world is critically corrected. Bethara Guru Dewa, the tritagonist, felt that he made a mistake by arranging life unjustly so that he was reminded by Kalakerna and had to agree with his request to keep the justice and preserve the world.